2005
DOI: 10.1016/j.amjhyper.2005.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated Liver Injury Induced by Ischemia–Reperfusion in Spontaneously Hypertensive Rats

Abstract: Background:The functions of polymorphonuclear leukocytes (PMNs), which play a critical role in organ damage, are primed in patients with essential hypertension and spontaneously hypertensive rats (SHR). Hepatic ischemia-reperfusion (I/R) injury is shown to be caused and aggravated by the PMNs. We examined whether the hepatic I/R injury was exaggerated in SHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Hypertension in the recipient or donor, longer CIT or WIT, and male donor were identified as risk factors of moderate to severe IRI. Ohmori et al reported that the counts of PMNs and their functions are elevated in hypertensive patients and spontaneously hypertensive rats (SHRs) compared to humans and normal rats, which, in turn, contributes to the development of liver IRI damage in hypertensive rats 34,35 . Of interest, an analysis of 3844 adult patients from the Scientific Registry of Transplant Recipients (SRTR) database indicated that hypertensive donor grafts are associated with poor prognosis in liver‐kidney transplantation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension in the recipient or donor, longer CIT or WIT, and male donor were identified as risk factors of moderate to severe IRI. Ohmori et al reported that the counts of PMNs and their functions are elevated in hypertensive patients and spontaneously hypertensive rats (SHRs) compared to humans and normal rats, which, in turn, contributes to the development of liver IRI damage in hypertensive rats 34,35 . Of interest, an analysis of 3844 adult patients from the Scientific Registry of Transplant Recipients (SRTR) database indicated that hypertensive donor grafts are associated with poor prognosis in liver‐kidney transplantation 36 .…”
Section: Discussionmentioning
confidence: 99%